Intellectual Imperialism:Definition, Traits, And Problems. - Alatas, Syed Hussein (2000)
Imperialism is not confined to the political or economic aspects of the historical process. Rather, it is to be considered as a cluster. A phenomenon such as imperialism is a cluster of different aspects of human undertakings.